Classroom management problems faced by education administrators in distance education during the pandemic period - Ece, Özlem; Bastas, Mert (Frontiers in Psychology, 2022)
Distance education contributes to the development of teamwork skills that may be needed in business life and builds effective collaborative communication skills that allow individuals to learn on their own. Students will be able to take online classes, interact with their teachers and become a member of this group. During a pandemic, countries face different constraints that change the perception of education. The use of distance education programs, especially during the recent global Covid-19 epidemic, has had a positive or negative impact on students and a positive or negative impact on teachers. The education sector has also been affected by the various measures taken by countries to minimize the risk of transmission during the pandemic period. In this period, the traditional understanding of education had to be interrupted, and teachers carried out their education and training activities in technological environments. Distance education has brought some difficulties as well as providing certain conveniences to teachers. Within the scope of this study, it has been tried to examine the problems faced by educators in classroom management in distance education during the pandemic period and solution proposals.